2022
DOI: 10.25176/rfmh.v22i2.4343
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes towards the covid-19 vaccine

Abstract: Objective:The objective of this research was to determine the relationship between the level of knowledge and attitudes towards the COVID-19 vaccine in the inhabitants of the province of Trujillo in the year 2021. Materials and methods:The type of study was applied, non experimental desing, with a quantitative approach, cross-sectional, and correlational level; a questionnaire for knowledge and attitudes was administered to a total of 500 adults in the province of Trujillo. Results: The results show that 88% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…This means that people with a high level of knowledge about the vaccine are more likely to have a positive perception of it than those with a low level of knowledge about it. Similarly, Aguilar Chávez et al (2021) concluded in their study that there is a significant relationship between the level of knowledge and attitudes towards the vaccine against COVID-19.…”
Section: Discussionmentioning
confidence: 94%
“…This means that people with a high level of knowledge about the vaccine are more likely to have a positive perception of it than those with a low level of knowledge about it. Similarly, Aguilar Chávez et al (2021) concluded in their study that there is a significant relationship between the level of knowledge and attitudes towards the vaccine against COVID-19.…”
Section: Discussionmentioning
confidence: 94%
“…Así también se cuenta con evidencia científica sobre la aceptación de vacunarse significativamente menor en la población con entorno o familiares fallecidos durante la pandemia. A causa de esto, hay múltiples elementos que influyen en el proceso de la aceptación ante la vacunación, puesto que la pandemia ha transcurrido con una gran desconfianza en la eficacia y seguridad de las vacunas, tanto así que ha generado actitudes negativas en las personas por el desconocimiento y mala información que circula en redes, desencadenando diferentes niveles de temor de la población en general (19).…”
Section: Resultsunclassified
“…A causa de esto, hay múltiples elementos que influyen en el proceso de la aceptación ante la vacunación, puesto que la pandemia ha transcurrido con una gran desconfianza en la eficacia y seguridad de las vacunas, tanto así que ha generado actitudes negativas en las personas por el desconocimiento y mala información que circula en redes, desencadenando diferentes niveles de temor de la población en general (19).…”
Section: Resultsunclassified